Laparoscopic gonedectomy in a case of complete androgen insensitivity syndrome - G Bhaskararao; Y Himabindu; Samir Ranjan Nayak; M Sriharibabu (Wolters Kluwer Medknow Publications, 2014)
Complete Androgen insensitivity syndrome is a disorder of hormone resistance characterized by a female phenotype in an individual with an XY karyotype. The pathogenesis of CAIS involves a defective androgen receptor gene located on X-chromosome at Xq11-12and end organ insensitivity to androgens, although androgen concentrations are appropriate for the age of the patient. There are three major types of androgen insensitivity syndrome: Complete androgen insensitivity syndrome, minimal androgen insensitivity syndrome, and partial androgen insensitivity syndrome. Management of androgen insensitivity syndrome includes multidisciplinary approach and involves gonedectomy to avoid gonadal tumors in later life. Hormone replacement therapy (HRT) and psychological support are required in long-term basis.